Modeling dynamic price dispersion of hotel rooms in a spatially agglomerated tourism city for weekend and midweek stays. Issue 8 (December 2019) - Mohammed, Ibrahim; Guillet, Basak Denizci; Law, Rob
In spite of the abundant evidence suggesting the existence of spatial agglomeration in the hotel industry and the potential for spatial econometric methods to contribute to the understanding on the effect of spatial competition on room pricing, limited research has been conducted in this regard. To contribute to this area of research, this study applied spatial models to examine online pricing data of hotels in Hong Kong to determine the effect of spatial agglomeration on dynamic or intertemporal price dispersion. The findings revealed that the magnitude of dynamic price dispersion is not only influenced by demand but also the pricing of neighboring hotels and hotel-specific attributes, such as number of rooms, star rating, chain affiliation, and scale. A major implication of this finding is that real-time tracking and analysis of neighboring hotels' prices could be an effective strategy to stay competitive in a spatially agglomerated environment.